2010
DOI: 10.4319/lo.2010.55.3.1009
|View full text |Cite
|
Sign up to set email alerts
|

Residual circulation due to internal waves shoaling on a slope

Abstract: We describe the residual circulation induced in a two-layer system when internal waves, with a wave length equal to or longer than the slope length, propagate over a sloping bottom and either reflect or break. For the case of no wave breaking, scaling is used to derive Boussinesq-type equations, the solution of which leads to an expression for the residual circulation adjacent to the sloping bottom. This residual circulation is maintained by a weak slope on the density interface. For breaking waves, laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 56 publications
2
64
0
2
Order By: Relevance
“…Marti & Imberger (2006) showed that a baroclinic density volume flux is set-up in the benthic boundary layer whenever a nonlinear density stratification exists in the lake, a condition that is nearly always present. Recently, Nakayama & Imberger (2010) have clarified this volume flux and showed that it may be sustained not only by a nonlinear density gradient, but also by differential mixing in the benthic boundary layer and nonlinear basin-scale internal wave breaking over a shoaling lake bottom. The current work has thus supplied the limiting link in the availability of re-generated nutrients.…”
Section: Nutrient/contaminant Diffusivitymentioning
confidence: 99%
“…Marti & Imberger (2006) showed that a baroclinic density volume flux is set-up in the benthic boundary layer whenever a nonlinear density stratification exists in the lake, a condition that is nearly always present. Recently, Nakayama & Imberger (2010) have clarified this volume flux and showed that it may be sustained not only by a nonlinear density gradient, but also by differential mixing in the benthic boundary layer and nonlinear basin-scale internal wave breaking over a shoaling lake bottom. The current work has thus supplied the limiting link in the availability of re-generated nutrients.…”
Section: Nutrient/contaminant Diffusivitymentioning
confidence: 99%
“…그러나 최근에는 컴퓨터의 발전과 함께 3차원 모델을 이용 하여 복잡한 지형과 경계조건을 고려한 성층 호수의 수리동 력학적 모의 연구가 가능해졌다 (Antenucci et al, 2000;Bernhardt and Kirillin, 2013;Chung et al, 2011;Hodges et al, 2000;Nakayama and Imberger, 2010;Shimizu et al, 2007). 본 연구의 목적은 Lake Tahoe에서 …”
Section: 난류경계층은 호 내 퇴적물의 재부상과 심층과 수온 전이unclassified
“…Field observations show basin-scale internal waves can interact with sloping topography where they shoal, reflect, and possibly break into a number of smaller scale waves as they adjust to the new environment (Helfrich and Melville 2006;Filatov et al 2012). Whether internal waves will shoal and break nearshore depends on the ratio of the boundary slope to wave slope, known as the internal Iribarren number j (Boegman et al 2005b;Aghsaee et al 2010;Nakayama and Imberger 2010). The magnitude of the internal Iribarren number is useful in the prediction of energy loss and mixing efficiency during breaking.…”
mentioning
confidence: 99%
“…This intensifies the benthic boundary layer updraft (Imberger and Ivey 1993) that plays a central role in the transport of nutrients and biological material from the hypolimnion to the euphotic zone (Marti and Imberger 2006;Bruce et al 2008). Moreover, the intrusion transports dissolved and resuspended material from the boundary to the center of the lake (Marti and Imberger 2006;Nakayama and Imberger 2010;Nakayama et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation